2006
DOI: 10.1159/000092232
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Acidified Toothpastes with Low Fluoride Content

Abstract: Fluoride toothpastes are a risk factor for the development of dental fluorosis. Products with low fluoride content offer a higher security, but their effectiveness must be proven. The aim of this in vitro study was to compare two acidified toothpastes with low fluoride concentration (412 and 550 µg F/g) with neutral toothpastes. Bovine enamel blocks were selected by surface microhardness (SMH) and randomized to twelve groups of 13, according to the fluoride concentration in toothpaste (placebo, 275, 412, 550 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
2
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 26 publications
3
46
2
7
Order By: Relevance
“…Zendium slurry (pH 5.21) and the Meridol slurry (pH 4.74) were slightly acidic and would be expected to provide higher F intensity than the neutral ones. Brighenti et al [2006] found a smaller decrease in percent SMH in a pH cycling model for 7 days when using acidified toothpastes compared to neutral ones. In our study no overall better performance could be shown of the slightly acidic toothpaste slurries compared to the neutral ones.…”
Section: Discussionmentioning
confidence: 80%
“…Zendium slurry (pH 5.21) and the Meridol slurry (pH 4.74) were slightly acidic and would be expected to provide higher F intensity than the neutral ones. Brighenti et al [2006] found a smaller decrease in percent SMH in a pH cycling model for 7 days when using acidified toothpastes compared to neutral ones. In our study no overall better performance could be shown of the slightly acidic toothpaste slurries compared to the neutral ones.…”
Section: Discussionmentioning
confidence: 80%
“…The use of bovine enamel has been verified in a number of in vitro studies to evaluate the effect of anticariogenic agents on enhancing enamel remineralization and inhibiting enamel demineralization [Brighenti et al, 2006;Lennon et al, 2006;ten Cate et al, 2006]. There are some reported variations in the characteristics of bovine enamel in comparison to human enamel; such as it provides a less variable response to both the cariogenic challenge and the anticariogenic agents, the composition of bovine enamel is less variable than human enamel [Mellberg, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…Among the in vitro models used worldwide, pH cycling simulates caries development under controlled condi- tions [White, 1995] and gives information on surface and subsurface enamel in caries dynamics [ten Cate and Mundorff-Shrestha, 1995]. The pH cycling model of Vieira et al [2005] for bovine teeth, based on the studies of ten Cate and Duijsters [1982] and Featherstone et al [1986], is a sensitive methodology for verifying the fluoride dentifrice dose-response relationship [Brighenti et al, 2006;Alves et al, 2007;Takeshita et al, 2009]. As a short-term pH cycling model, it provides a lower demineralization and a surface layer and lesion depth considered 'small'.…”
Section: Discussionmentioning
confidence: 99%